2024
DOI: 10.1039/d3cp05044k
|View full text |Cite
|
Sign up to set email alerts
|

The slow Arrhenius process in small organic molecules

Federico Caporaletti,
Simone Napolitano

Abstract: Experimental observation of the Slow Arrhenius process in small organic molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In the context of soft-clusters, τ cm exhibits analogous features with respect to N be . At the possible segmental level, Napolitano et al have recently identified a slow Arrhenius process (SAP) that is decoupled from the α-relaxation. The SAP concept provides valuable insights into future investigations in this direction.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of soft-clusters, τ cm exhibits analogous features with respect to N be . At the possible segmental level, Napolitano et al have recently identified a slow Arrhenius process (SAP) that is decoupled from the α-relaxation. The SAP concept provides valuable insights into future investigations in this direction.…”
Section: Resultsmentioning
confidence: 99%
“…Recently another mechanism of relaxations has been observed via experiments for a large class of materials including small organic molecules in addition to polymers. 91 Named the slow Arrhenius process (SAP), it is found to be active above and below the T g . 92 The SAP has temperature-independent activation energy spanning temperatures ranging from below T g to well above it and has been found to follow the enthalpy− entropy compensation rule.…”
Section: Viscosity Modulus Relaxation and Diffusionmentioning
confidence: 99%
“…At temperatures well above T g , the β-relaxations merge with theα-relaxations and are not distinguishable. Recently another mechanism of relaxations has been observed via experiments for a large class of materials including small organic molecules in addition to polymers . Named the slow Arrhenius process (SAP), it is found to be active above and below the T g .…”
Section: Relevant Aspects In Confined Glassy Polymer Filmsmentioning
confidence: 99%
“…Intriguingly, the low-frequency peak, associated with the SAP, exhibits a stronger h dependence. The SAP is a molecular process observed in more than 30 systems including polymers and small molecules, both above and below their glass transition temperature. Differently than other processes slower than the α-relaxation at T > T g , the thermal barrier of the SAP is temperature-independent and this quantity is sufficient to uniquely determine the experimental time scale of the process .…”
mentioning
confidence: 99%